A Brief Review of Network and Sensor Virtualization for Wireless Sensor Networks - Ijaz, Amir; Babich, Fulvio (International Journal of Sensors Wireless Communications and Control, 2015)
Wireless Sensor Networks (WSNs) are more vigorously being used with applications relating to the Internet of Things (IoT). They are used for a variety of applications, but are frequently deployed keeping in view a specific objective. Sensor network virtualization may be classified as network and sensor virtualization. Virtualization comes with numerous challenges in the form of segregating various networks, hardware and associated software in the system. This research paper touches upon the past and current research directions associated with virtualization, various design targets, layouts and numerous testbeds have also been looked into. The paper also highlights the current challenges and future avenues associated to expedite research on virtualization.
Keywords: Internet of things (IoT)